2019
DOI: 10.1177/1420326x19855421
|View full text |Cite
|
Sign up to set email alerts
|

Development of a natural light reproduction system for maintaining the circadian rhythm

Abstract: Circadian rhythm is linked to sleep, arousal and human health overall, affecting body temperature and heart rate. A 24-h natural-light cycle provides optimum lighting environment for humans. However, as people increasingly stay indoors with artificial lighting, lacking periodic characteristics, imbalance in the circadian rhythm ensues. Previous lighting-related studies to resolve such problem partially provided the colour temperatures of natural light but failed to reproduce the 24-h periodic characteristics o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 18 publications
0
11
0
1
Order By: Relevance
“…(c‐ no filter) Since natural light includes all possible vibration directions perpendicular to the light propagation direction, no filter was added. [ 31 ]…”
Section: Degradation Experimentsmentioning
confidence: 99%
“…(c‐ no filter) Since natural light includes all possible vibration directions perpendicular to the light propagation direction, no filter was added. [ 31 ]…”
Section: Degradation Experimentsmentioning
confidence: 99%
“…Jain and Garg examined the presentation and attainability of different sunlight determining techniques and their application in controlling blinds and incorporated lighting frameworks [6]. Kim et al proposed a characteristic light multiplication framework that gives the sunshine cycle attributes of regular light to keep up with circadian rhythms [7]. Singh et al have studied developing a complete proof system that requires the development and integration of various technologies that can be used to develop smart homes [8].…”
Section: Related Workmentioning
confidence: 99%
“…At this point, each wavelength was classified into the following wavelength bands: 380–480 nm for short-wavelength, 480–560 nm for middle wavelength, and 560–780 nm for long wavelength. The band-by-band ratio of each wavelength was calculated using Equation (1) [ 13 ]. …”
Section: Characterization Of Natural Lightmentioning
confidence: 99%
“…A precedent study showed that the characteristics of a spectrum or the color temperature of natural light contributes to maintaining human body circadian rhythms [ 8 , 9 ] and showed that the characteristics of a certain short-wavelength band (460 or 446–488 nm) are related to sleeping and wake-up cycles [ 10 , 11 , 12 ]. Kim et al analyzed the characteristics of natural light collected through an experimental test and suggested a standard for controlling the circadian color temperature of natural light to support the circadian rhythm [ 13 ]. Moreover, in the lighting field, LED light sources and lighting products for realizing the spectral characteristics of natural light have been developed [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation